Pemantauan Dampak Kekeringan Lahan Pertanian di Lamongan Menggunakan NDVI Berbasis SIG - Bara Ramadani Wijaya; Nur Azizah Affandy; Salwa Nabilah (Universitas Darul Ulum, 2024)
Drought trends are occurring throughout Indonesia, including in Lamongan Regency. The problems caused by drought significantly affect the agricultural sector in Lamongan, with varying impacts each year. This study uses the Normalized Difference Vegetation Index (NDVI) method integrated with Geographic Information Systems (GIS) to monitor and analyze vegetation conditions as an indicator of drought. Based on the Landsat 8 imagery analysis from August to October 2019-2021, the results show significant changes in vegetation conditions related to drought. The year 2020 showed a decrease in areas with high greenness, while 2021 showed a significant recovery. This vegetation monitoring is expected to serve as a basis for more effective drought mitigation policies for the agricultural sector in Lamongan Regency.